Respiratory function in adult patients with spinal muscular atrophy treated with nusinersen – a monocenter observational study - Wurster, Claudia Diana; Uzelac, Zeljko; Dreyhaupt, Jens; Schuster, Joachim; Dorst, Johannes; Ludolph, Albert Christian; Wollinsky, Kurt (Frontiers in Neurology, 2024)
Background/objective Insufficiency of respiratory muscles is the most important reason for mortality in the natural history of SMA. Thus, improvement or stabilization of respiratory function by disease-modifying therapies (DMT) is a very important issue. Methods We examined respiratory function using forced vital capacity (FVC) in 42 adult SMA patients (2 SMA type 1, 15 SMA type 2, 24 SMA type 3, 1 SMA type 4, median age 37 years, range 17–61 years) treated with nusinersen for a median of 22.1 months (range 2.1 to 46.7 months). Change in FVC was assessed using mixed effects linear regression models. Results Baseline FVC differed significantly between SMA type 1 (4.0, 8.0%), 2 (median 22.0%, IQR 18.0–44.0), 3 (median 81.0%, IQR 67.0–90.8) and, respectively, type 4 (84.0%) patients reflecting the heterogeneity of respiratory impairment based on the SMA type in adulthood (p < 0.0001). FVC remained stable during follow-up (mean −0.047, 95% CI −0.115 to 0.020, p = 0.17); however, subgroup analysis showed an increase in FVC of type 2 patients (mean 0.144, 95% CI 0.086 to 0.202, p < 0.0001) and a decrease in FVC of type 3/4 patients (−0.142, 95% CI −0.239 to −0.044, p = 0.005). Conclusion The observed improvement in FVC in patients with SMA type 2 can be seen as a therapeutic response differing from the progressive decline typically seen in the spontaneous course. For SMA type 3/4 patients approaching normal spirometry at baseline, FVC may only be of limited use as an outcome parameter due to ceiling effects.